2021
DOI: 10.1021/acs.langmuir.1c01383
|View full text |Cite
|
Sign up to set email alerts
|

The Operating Cycle of NO Adsorption and Desorption in Pd–Chabazite for Passive NOx Adsorbers

Abstract: Pd-doped chabazite (Pd/CHA) offers unique opportunities to adsorb and desorb NO x in the target temperature range for application as a passive NO x adsorber (PNA). The ability of Pd/CHA to trap NO x emissions at low temperatures (<200 °C) is facilitated by the binding of NO x species at various Pd sites available in the CHA framework. Density functional theory (DFT) simulations are performed to understand Pd speciation in CHA and the interaction of NO with Pd/CHA to explain the mechanisms of NO adsorption,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 34 publications
2
27
1
Order By: Relevance
“…To further improve the sensing behavior of pure nanomaterials, the doping of elements are the most common strategies. Transition metal elements are commonly applied in surface modification and performance optimization, and previous research has proved that the sensing properties of materials are improved significantly after substitutional doping with transition metal elements. , For example, substitutional doping of WSe 2 monolayer with transition metal elements (Pd, Ag, Au, Pt) have been studied for its adsorption performance toward CO 2 , NO 2 , and SO 2 . It is found that, compared with pristine WSe 2 monolayer, doped WSe 2 has a great effect on the adsorption of these gas molecules.…”
Section: Introductionmentioning
confidence: 99%
“…To further improve the sensing behavior of pure nanomaterials, the doping of elements are the most common strategies. Transition metal elements are commonly applied in surface modification and performance optimization, and previous research has proved that the sensing properties of materials are improved significantly after substitutional doping with transition metal elements. , For example, substitutional doping of WSe 2 monolayer with transition metal elements (Pd, Ag, Au, Pt) have been studied for its adsorption performance toward CO 2 , NO 2 , and SO 2 . It is found that, compared with pristine WSe 2 monolayer, doped WSe 2 has a great effect on the adsorption of these gas molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Previous theoretical studies on Pd zeolites used both semilocal and hybrid functionals. [62][63][64][65][66][67][68][69][70][71]84 Mei et al 67 obtained similar energies of NO adsorption in Pd-HBEA using Perdew− Burke−Ernzerhof (PBE) 85 and Heyd−Scuseria−Ernzerhof (HSE06) 86 functionals. However, Mandal et al 64 found significant dependence of NO adsorption energies on the type of exchange−correlation (XC) functional, with more exothermic NO adsorption energies for the PBE functional compared to the HSE06 functional.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical methods have been utilized only in a few studies of Pd zeolites with the focus on PNA. Khivantsev et al showed that Pd ions in Pd-SSZ-13 are present as super electrophilic Pd 2+ species. Mandal et al concluded that Pd II preferentially populates 2Al sites in the six-membered rings (6MRs), while the formation of ZPd II OH in 1Al sites is energetically prohibitive.…”
Section: Introductionmentioning
confidence: 99%
“…11,12,26,27,38 The assumption of dimeric sites allows formulating mechanisms in which Pd takes formal oxidation states of +2 and +1 and avoids the complete reduction to metallic Pd. The complete mechanisms with elementary steps reported so far involve the formation of dimeric sites 27,39,40 while the reported mechanism on monomeric Pd sites by Mei et al does not explain the full catalytic cycle. 38 These mechanisms are inconsistent with the molecular chemistry (involving 1/2 O 2 ) but also with characterization of Pd-exchanged CHA showing only atomically dispersed Pd atoms in the zeolite framework in their study.…”
Section: Introductionmentioning
confidence: 84%